Biophysical study of G-quadruplex structures in solution and G-wire superamolecular assembly on graphene - Hu, Lanying (2012)
Guanine-rich nucleic acid sequences have a high propensity to adopt non-B DNA secondary structures like G-quadruplexes. Sequences that could potentially form G-quadruplexes are widespread throughout the genome and found to be more prominent in biologically critical regions. They may play biological significant roles in telomere maintenance, as well as regulation of gene transcription, replication and recombination.